2016
DOI: 10.1159/000446919
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Intracellular Adhesion Molecule-1 in Patients with Unipolar or Bipolar Affective Disorders: Results from a Pilot Trial

Abstract: Background: Immunological and vascular markers may play a role in the pathophysiology of mood disorders and mood changes. Aim: To test whether the cell adhesion molecule soluble intracellular adhesion molecule-1 (sICAM-1) may serve as a biomarker for patients with unipolar or bipolar affective disorders when compared to a healthy control group, and whether sICAM-1 blood levels change during different mood states. Methods: sICAM-1 serum concentrations were compared between 20 healthy controls and 48 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…It is possible that these proteins are over-expressed in more chronic affective disorders and could implicate Th2 inflammation in this subpopulation. sICAM1, sVCAM1 and MCP1 are notably lower in this sample of inpatients than controls, unexpected as these chemoattractants function as part of a pro-inflammatory response and have in a few studies been reported as elevated in depression (Dimopoulos et al, 2006;Schaefer et al, 2016). Although highly speculative, it is possible that low circulating immunoglobulin levels may suggest that they have penetrated the blood-brain-barrier into the brain (Takeshita and Ransohoff, 2012), a possibility that we were not able to examine.…”
Section: Does An Inflammatory State Reflect Prior Treatment-resistantmentioning
confidence: 70%
“…It is possible that these proteins are over-expressed in more chronic affective disorders and could implicate Th2 inflammation in this subpopulation. sICAM1, sVCAM1 and MCP1 are notably lower in this sample of inpatients than controls, unexpected as these chemoattractants function as part of a pro-inflammatory response and have in a few studies been reported as elevated in depression (Dimopoulos et al, 2006;Schaefer et al, 2016). Although highly speculative, it is possible that low circulating immunoglobulin levels may suggest that they have penetrated the blood-brain-barrier into the brain (Takeshita and Ransohoff, 2012), a possibility that we were not able to examine.…”
Section: Does An Inflammatory State Reflect Prior Treatment-resistantmentioning
confidence: 70%
“…Recently, additional novel cytokines and chemokines have yielded evidence of abnormalities in depression. These include: macrophage inhibitory protein 1a, IL-1a, IL-7, IL-12p70, IL-13, IL-15, eotaxin, granulocyte macrophage colony-stimulating factor, 57 IL-5, 58 IL-16, 59 IL-17, 60 monocyte chemoattractant protein-4, 61 thymus and activation-regulated chemokine, 62 eotaxin-3, TNFb, 63 interferon gamma-induced protein 10, 64 serum amyloid A, 65 soluble intracellular adhesion molecule 66 and soluble vascular cell adhesion molecule 1. 67 …”
Section: Introductionmentioning
confidence: 99%
“…First, sICAM-1 is elevated in atherosclerosis, myocardial infarction, and cardiovascular diseases, indicating its potential as a biomarker for vascular inflammation ( Hwang et al., 1997 ; Noutsias et al., 2003 ; Ridker et al., 1998 ). Second, increased sICAM-1 is related to the development of neurological diseases such as depression ( Schaefer, Sarkar, Schwarz, & Friebe, 2016 ). In addition, sICAM-1 is responsible for inflammatory processes in terms of neuropathology.…”
Section: Discussionmentioning
confidence: 99%